The Influence of Whatsapp Group on Descriptive Text Writing Ability of the Tenth Grade Students of SMK Al-Achyar in the 2019/2020 Academic Year - Selvy Kurniasari; Tri Mulyati; Sutami Dwi Lestari (LUNAR, 2021)
The objective of the research is to know whether the students taught by using WhatsApp group get better descriptive text writing score. The research design of this research was pre-experimental research. The respondents of this research were the tenth grade students of TKJ class at SMK Al-Achyar, consisting of 19 students. To collect the data the researcher used test as the instrument. The data were collected through writing test. The test was given before and after the treatment. On the treatment, the researcher used WhatsApp Group as a media in teaching and learning writing descriptive text. The computation result of t-test was 6.93. The result of computation value was consulted to the